Further studies on the mode of action of calcitonin on isolated rat osteoclasts: pharmacological evidence for a second site mediating intracellular Ca2+ mobilization and cell retraction. - Alam, A; Bax, C; Shankar, V; Bax, B; Bevis, P; Huang, C; Moonga, B; Pazianas, M; Zaidi, M (1993)
Calcitonin is a circulating polypeptide that inhibits bone resorption by inducing both quiescence (Q effect) and retraction (R effect) in osteoclasts. Two structurally related members of the calcitonin gene peptide family, calcitonin gene-related peptide (CGRP) and amylin, inhibit osteoclastic bone resorption selectively via the Q effect. In the present study, we have made measurements of cell spread area in response to the application of amylin, CGRP and a peptide fragment of CGRP, CGRP-(Val8Phe37). We found that, over a wide concentration range (50 pmol/l to 2.5 mumol/l), the selective Q effect agonists did not produce an R effect. Furthermore, the peptides, when used at a 50-fold higher molar concentration than calcitonin, did not antagonize calcitonin-induced cell retraction. Additionally, experiments designed to measure changes in the intracellular free calcium concentration ([Ca2+]i) in single osteoclasts revealed that, unlike calcitonin, the non-calcitonin Q effect agonists did not produce a rise in [Ca2+]i. The peptides were also unable to attenuate the peak rise in [Ca2+]i induced by calcitonin. The results support our hypothesis that the inhibitory activity of calcitonin on osteoclastic bone resorption is mediated by two sites which may or may not be part of the same receptor complex. One of these is the classical Q effect site coupled to adenylate cyclase via a cholera toxin-sensitive Gs. This site can be activated by nanomolar concentrations of calcitonin, amylin, CGRP or CGRP-(Val8Phe37). A novel R effect site, possibly coupled via a pertussis toxin-sensitive G protein to a [Ca2+]i elevating mechanism is predicted from this study.(ABSTRACT TRUNCATED AT 250 WORDS)